COUNTER-RADICALISM MOVEMENT AND HYBRIDIZATION OF IDENTITY IN THE YOUNG INTERFAITH COMMUNITY IN YOGYAKARTA - M. Naufal Waliyuddin (International Conference on Social and Islamic Studies, 2021)
The radicalism discourse that has been quite widespread in the last two decades has produced various responses, ranging from counter-narrative, de-radicalization, and counter-radicalism efforts. This paper investigates specifically how efforts to counter radicalism are pursued from civil society initiatives, one of which is Young Interfaith Peacemaker Community (YIPC) in Yogyakarta. Using an interpretative phenomenological approach, this qualitative research explores several motives behind the counter-radicalism movement that they organize and are equipped with a visible hybrid portrait of identity. Observation, informal interviews, and documentation are operated as data retrieval techniques. The literature review was also deepened to elaborate data and develop argumentative narratives. The results obtained show that the three dialectical reasons that trigger them to counter radicalism are a collective awareness, imagined common enemy, and claims of youthfulness. In particular, the hybridization of identity that has been captured in this community can also be observed in changes in attitude, perspective, and behavior patterns of individuals—before joining and when joining YIPC Yogyakarta. Borrowing from Gadamer’s concept, this was due to the mixture of horizons which later gave birth to a fused or assimilated character (hybrid) and reflected in their speech, attitudes, social media content, and social actions.